2022
DOI: 10.1186/s13000-022-01233-4
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic synovial sarcomas of the liver: a case report and literature review

Abstract: Background Synovial sarcoma is a soft tissue sarcoma of temporarily unknown histologic origin with the ability for biphasic differentiation, occurring mostly in the vicinity of large joints of the extremities. Synovial sarcoma that originates in the liver is extremely rare. Only 7 cases have been reported in the domestic and international literature. Case presentation We report an 11-year-old female patient who underwent partial hepatectomy for a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Whereas myogenin, CK20, PAX-8, WT-1, SMA, S-100, CD34 and desmin were negative. 5 In support with the above studies the IHC analysis in our case also showed that SMA, CD 99, Vimentin, Bcl-2 and CD 68 were positive in spindle cell component. Pan CK and p63 showed nuclear expression in epithelial component.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Whereas myogenin, CK20, PAX-8, WT-1, SMA, S-100, CD34 and desmin were negative. 5 In support with the above studies the IHC analysis in our case also showed that SMA, CD 99, Vimentin, Bcl-2 and CD 68 were positive in spindle cell component. Pan CK and p63 showed nuclear expression in epithelial component.…”
Section: Discussionsupporting
confidence: 91%
“…The studies concluded that it is an important basis for the diagnosis of synovial sarcoma. 5 However, we could not do the molecular study since the patient was not affordable.…”
Section: Discussionmentioning
confidence: 99%